The impact of network convergence on telecommunications software. - Moyer, S.
This describes a converged network architecture and then discusses why it needs to be open and programmable and how this can be accomplished. A discussion of two approaches to open/programmable networks-JAIN and Parlay-is provided to highlight the key ideas. The converged network is a key player in e-business and the next-generation applications currently being developed for the growing digital economy. We discuss the role of telecommunications bandwidth trading and application integration in next-generation applications (NGAs) and their relevance to converged networks. Some of the challenges software engineers and programmers can expect to encounter while trying to build these networks are also discussed
Keywords: API; Internet; Internet telephony; JAIN; Java; PSTN; Parlay; Application integration; Digital economy; E-business.; Integrated networks; Network architecture; Network convergence; Next-generation applications; Open architecture; Open/programmable networks; Programmable architecture; Public switched telephone network; Software engineers; Software programmers; Telecommunications bandwidth trading; Telecommunications software; Telephone networks